SORTOUT‐AB: A Study of Race to Understand Alzheimer Biomarkers. (20th December 2022) - Xiong, Chengjie; Wolk, David A.; Lah, James J.; Gleason, Carey E.; Roberson, Erik D; Benzinger, Tammie L.S.; Schindler, Suzanne E.; Fagan, Anne M.; Hassenstab, Jason J.; Moulder, Krista L.; Balls‐Berry, Joyce E; Sperling, Reisa A.; et al.
Abstract: Background: Ethno‐racial factors may influence the multifactorial etiology and heterogeneity of Alzheimer Disease (AD). Given the conflicting reports on racial differences in AD, well‐powered cohort studies are needed to identify differences in AD biomarkers between racialized groups. Method: This NIH‐funded study aims to determine cross‐sectional and longitudinal differences in AD biomarkers between self‐reported Black/African Americans (AA) and non‐Hispanic Whites. It implements a longitudinal design with centralized and standardized analyses of cerebrospinal fluid (CSF) and plasma samples, MRI and amyloid and tau PET scans, and harmonized clinical/cognitive outcomes. It leverages available retrospective biofluid samples and brain scans, and prospectively collected data from four ADRCs (Washington University (WU), University of Pennsylvania, Emory University, University of Alabama), and the study of African Americans Fighting Alzhiemer's in Midlife (AA‐FAIM)), in addition to the derived data from the Harvard Aging Brain Study and the Anti‐Amyloid Treatment in Asymptomatic Alzheimer's (A4) trial. It will further determine the roles of major risk factors and Social and Structural Determinants Influencing Aging and Dementia (SS‐DIAD) in racial differences. Results: By 12/31/2021, ∼3114 CSF samples, 4896 MRI scans, 3754 amyloid PET scans, and 998 tau PET scans retrospectively collected across studies were transferred to WU Knight ADRC Fluid Biomarker and Imaging Cores. CSF Aβ42, Aβ40, Tau, pTau181, and NfL were measured from all CSF samples. A subset of 3687 MRI scans and 2336 amyloid PET scans were re‐processed. Preliminary analyses on data from 179 AAs and 1180 Whites (all CDR 0 at baseline) indicated that baseline CSF Tau and pTau181 were lower, and Aβ42/Aβ40 was higher, in AAs compared to Whites. Longitudinally, CSF Aβ42/Aβ40 declined more slowly, and amyloid (PET) uptake and CSF Tau (pTau181) increased more slowly, in AAs than Whites. Additionally, a multi‐domain battery of SS‐DIAD was pilot tested, and revealed high test‐retest intraclass correlations (ICC>=0.83) for multiple domains, facilitating a uniform collection of SS‐DIAD across sites. Conclusion: It is feasible to harmonize biomarker data and SS‐DIAD across multiple studies to understand cross‐sectional and longitudinal ethno‐racial differences in AD. Preliminary analyses suggest cross‐sectional and longitudinal differences in both amyloid and tau biomarkers between self‐reported AA and Whites.